Rancang bangun alat cutting wire dengan kontrol CNC untuk meningkatkan tingkat presisi dan efisiensi bahan baku menggunakan software max 3 - Widiyanto, Sigit; Saputra, Alfian Ady; Wiguna, Gun Gun; Prayitno, Pungkas (Jurnal Teknik Mesin Indonesia, 2024)
The CNC machine is a development of a conventional machine tool, in which control changes from manual to automatic, by following a program that has been made. There are many types of tools for cutting wire, and some even still use simple tools and operate manually. What will be discussed in this study is a method with several stages including finding the cutting force, material diameter, pneumatic cylinder diameter to be used, required motor power, tension in the frame and welding joints. In this design, the material to be processed is copper wire with a tensile strength of 200 N⁄mm2, the cutting force to be used is 402 N, with a pneumatic cylinder diameter of 44 mm (used is 50 mm size), the motor power used is 0.039 kW or 39 W (the power of the motor is 48 W), the shaft to be used is 6.3 mm in diameter, the connection to be used is in the form of a threaded thread with type M4 said to be safe because Sf on the thread is 6 (< 11.17), the frame material to be used is SS400 iron, it is said to be safe because on the pillar frame (1) is 0.047 N)⁄mm2 (< 39.2 N⁄mm2), and for the sectional frame (2) is 0.774 N⁄mm2 (< 40.18 N⁄mm2), the connection using welding is said to be safe because in the frame (1) is 6.96 N⁄mm2 (< 91.63 N⁄mm2), and in frame welding (2) is 0.0469 N⁄mm2 (< 91.63 N⁄mm2).